The Lipid Profile and Aorta Histopathology On Hyperlipidemic Rat by Saurauia vulcani Korth. Leaves Extract - Octora, Debi Dinha; Rosidah; Silalahi, Jansen; Satria, Denny (Talenta Publisher, 2023)
Abstract. Dyslipidemia is a pathological condition characterized by increased levels of total cholesterol, triglycerides and LDL and decreased levels of HDL. Dyslipidemia causes cardiovascular disease risk factors by increasing cholesterol levels, increasing triglyceride levels, lowering HDL levels, and increasing LDL levels, as well as decreasing the proliferation of cardiac aortic cells in dyslipidemic rats. The pirdot plant (Saurauia vulcani Korth.) has long been known by the Simalungun, Toba and Karo communities to have the potential to treat various diseases caused by disruption of lipid processes in the body. Pirdot leaves contain bioactive compounds of flavonoids, tannins and saponins that have the potential to improve lipid profiles and prevent cardiovascular disease. This study aims to determine the activity of EEDP on the lipid profile of dyslipidemic rats. Pirdot leaf simplicia powder was extracted by maceration with 96% ethanol solvent and the extract was used on 30 dyslipidemic rats which were divided into 6 groups. Group 1 (Na-CMC), group 2 (Atorvastatin), group 3, 4, 5, 6 EEDP doses of 50, 100, 200, 400 mg/kg BW were administered orally for 21 days. At the end of the treatment, the levels of total cholesterol (TC) and aortic cell proliferation were measured. The results showed that Saurauia vulcani Korth had water content (6.23%), water soluble extract (10.50%), simplicia content soluble in ethanol (14.77%), total ash content (7.05%) and acid insoluble ash content (0.48%). From the antidyslipidemic study it was shown that EEDP 400 mg/kg BW improved blood lipand to increase aortic cell proliferation dyslipidemic rats was 69.84Â±0.27. Based on the explanation above, it is concluded that EEDP has an antidyslipidemic effect.